PROTEIN PROFILE AND MDA SPERMATOZOA LEVELS OF HYPERGLYCEMIC MICE FED BY BEAN SPROUTS EXTRACT - Hidayat, Erwin; Susanti, R.; Marianti, Aditya (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2015)
Hyperglycemic conditions lead increased lipid peroxide and MDA which would damage structure and fluidity membrane so that impaired membrane function. Vitamin E on sprouts is an antioxidant that is capable of maintaining the integrity of cell membranes. Twenty eight mice which were grouped into 4 groups: control , P1, P2 and P3. Hyperglycemic treatment is by injecting of monohidrate alloxan dose of 150 mg/kgbw in group (P1, P2 and P3). Preparation and injecting of bean sprouts extract dose of 50 mg/20gbw to P2 and 100 mg/20gbw to P3 on 30 days.Taking of sperm to sperm protein isolation, and then analysis of protein molecular weight, testing MDA TBARS method. Based on the research results of the analysis protein profiles found in the control and P3 to be 8 protein bands is 72, 60, 49, 42, 35, 30, 28, and 23 kDa. While the P1 and P2 protein band 42 kDa are not found. Results of the analysis showed MDA significant different, control group is 2.43 nmol/ml, P1 7.89 nmol/ml, P2 5.19 nmol/ml and P3 3.29 nmol/ml. Concluded that the bean sprouts extract dois 100 mg/20ggw shows a significance influence on recovery protein profiles and MDA levels spermatozoa of hyperglycemic mice.Keywords: Protein profile, MDA, Hyperglycemic, Bean sprouts